Generating competitive advantage through competitor information systems - Ala-Kurikka, Sanna (My University, 2014)
This pro gradu –thesis discusses generating competitive advantage through competitor information systems. The structure of this thesis follows the structure of the WCA model by Alter (1996). In the WCA model, business process is influenced by three separate but connected elements: information, technology, and process participants. The main research question is how competitor information can be incorporated into or made into a tool creating competitive advantage. Research subquestions are: How does competitor information act as a part of the business process creating competitive advantage? How is a good competitor information system situated and structured in an organisation? How can management help information generate competitive advantage in the business process with participants, information, and technology? This thesis discusses each of the elements separate, but the elements are connected to each other and to competitive advantage. Information is discussed by delving into competitor information and competitor analysis. Competitive intelligence and competitor analysis requires commitment throughout the organisation, including top management, the desire to perform competitive intelligence and the desire to use the end products of that competitive intelligence. In order to be successful, systematic competitive intelligence and competitor analysis require vision, willingness to strive for the goals set, and clear strategies to proceed. Technology is discussed by taking a look into the function of the competitor information systems play and the place they occupy within an organization. In addition, there is discussion about the basic infrastructure of competitor information systems, and the problems competitor information systems can have plaguing them. In order for competitor information systems to be useful and worthy of the resources it takes to develop and maintain them, competitor information systems require on-going resource allocation and high quality information. In order for competitor information systems justify their existence business process participants need to maintain and utilize competitor information systems on all levels. Business process participants are discussed through management practices. This thesis discusses way to manage information, technology, and process participants, when the goal is to generate competitive advantage through competitor information systems. This is possible when information is treated as a resource with value, technology requires strategy in order to be successful within an organization, and process participants are an important resource. Generating competitive advantage through competitor information systems is possible when the elements of information, technology, and business process participants all align advantageously.